2021
DOI: 10.3748/wjg.v27.i16.1785
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of MRPL35 inhibits gastric carcinoma cell proliferation by regulating downstream signaling proteins

Abstract: BACKGROUND Gastric carcinoma (GC) is a digestive system disease with high morbidity and mortality. However, early clinical detection is difficult, and the therapeutic effect for advanced disease is not satisfactory. Thus, finding new tumor markers and therapeutic targets conducive to the treatment of GC is imperative. MRPL35 is a member of the large subunit family of mitochondrial ribosomal protein. MRPL35 shows the characteristic of oncogene in colorectal cancer and esophageal cancer, which promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…MRPL35 expression is upregulated in GC and is associated with a poor prognosis. Cell functional studies have revealed that the knockdown of MRPL35 inhibits cell proliferation in GC via related proteins, including PICK1, Bcl-xL, and AGR2 (84). High expression of MRPS29 in GC is associated with a better prognosis, and the downregulation of MRPS29 expression could increase resistance to chemotherapy by inhibiting apoptosis and promoting cell migration, consistent with the pro-apoptotic function of MRPS29 (85).…”
Section: Prognosismentioning
confidence: 75%
“…MRPL35 expression is upregulated in GC and is associated with a poor prognosis. Cell functional studies have revealed that the knockdown of MRPL35 inhibits cell proliferation in GC via related proteins, including PICK1, Bcl-xL, and AGR2 (84). High expression of MRPS29 in GC is associated with a better prognosis, and the downregulation of MRPS29 expression could increase resistance to chemotherapy by inhibiting apoptosis and promoting cell migration, consistent with the pro-apoptotic function of MRPS29 (85).…”
Section: Prognosismentioning
confidence: 75%
“…The down-regulated expression of MRPL35 can increase reactive oxygen species (ROS) levels, correlating with DNA damage [ 23 ]. Increased ROS levels may lead to more extensive and irreparable cell damage via DNA oxidation [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…After filtering using the LASSO algorithm, three core genes remained: PLCD3, MRPL35 and CYP2S1. Studies have reported the tumor-promotive role of PLCD3 in thyroid cancer ( 32 ) and osteosarcoma ( 33 ), the role of MRPL35 in gastric ( 34 ) and colorectal ( 35 ) cancer, and the role of CYP2S1 in breast ( 36 ) and lung ( 37 ) cancer. Consistent with this, the group with high WF scores, calculated for the three genes, showed significantly worse outcomes compared with those with low WF scores.…”
Section: Discussionmentioning
confidence: 99%